2014
DOI: 10.1111/nejo.12074
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Justice and Conflict Management at School

Abstract: In this research, we explored the contributions of perceived procedural justice (PPJ) to the conflict management behaviors of adolescents when they experience conflict with their teachers.We tested an extensive model to determine how PPJ contributes to conflict management. We also extended research on PPJ to examine its impact on adolescents. Our results, acquired from a large and diverse sample of 256 high school students, indicate that PPJ had an impact on adolescents' approach to managing conflicts with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 92 publications
2
16
0
3
Order By: Relevance
“…Fairness has consistently been emphasized in classroom assessment (CA) standards and practices as an essential quality and a significant dimension of teachers' assessment literacy (DeLuca, 2012;DeLuca, LaPointe-McEwan, & Luhanga, 2016;Xu & Brown, 2016). Empirical studies have demonstrated that teachers' fairness practices are associated with positive learning effects for students such as cognitive learning (Holmgren & Bolkan, 2014;Molinari, Speltini, & Passini, 2013), instructor satisfaction (Wendorf & Alexander, 2005), self-efficacy (Vallade, Martin, & Weber, 2014), legitimation of teacher and school authority (Gouveia-Pereira, Vala, Palmonari, & Rubini, 2003;Nelson, Shechter, & Ben-Ari, 2014), political trust (Abdelzadeh, Zetterberg, & Ekman, 2015), and positive evaluation of teacher expertise (Cronen & Fuller, 1976;Gotlieb, 2009;Rodabaugh & Kravitz, 1994). In contrast, perceived unfair behavior is associated with outcomes such as aggression and hostility (Horan, Chory, Carton, Miller, & Raposo, 2013;Uludag, 2014), truancy (Ishak & Fin, 2013), headache (Lenzi et al, 2013), and cheating (Lemons, Martin, & Seaton, 2011).…”
mentioning
confidence: 99%
“…Fairness has consistently been emphasized in classroom assessment (CA) standards and practices as an essential quality and a significant dimension of teachers' assessment literacy (DeLuca, 2012;DeLuca, LaPointe-McEwan, & Luhanga, 2016;Xu & Brown, 2016). Empirical studies have demonstrated that teachers' fairness practices are associated with positive learning effects for students such as cognitive learning (Holmgren & Bolkan, 2014;Molinari, Speltini, & Passini, 2013), instructor satisfaction (Wendorf & Alexander, 2005), self-efficacy (Vallade, Martin, & Weber, 2014), legitimation of teacher and school authority (Gouveia-Pereira, Vala, Palmonari, & Rubini, 2003;Nelson, Shechter, & Ben-Ari, 2014), political trust (Abdelzadeh, Zetterberg, & Ekman, 2015), and positive evaluation of teacher expertise (Cronen & Fuller, 1976;Gotlieb, 2009;Rodabaugh & Kravitz, 1994). In contrast, perceived unfair behavior is associated with outcomes such as aggression and hostility (Horan, Chory, Carton, Miller, & Raposo, 2013;Uludag, 2014), truancy (Ishak & Fin, 2013), headache (Lenzi et al, 2013), and cheating (Lemons, Martin, & Seaton, 2011).…”
mentioning
confidence: 99%
“…Reliabilities (measured by Cronbach's alpha) of the questionnaires were as follow: neutrality (e.g., “my spouse explains his/her decisions to me”) yielded alpha = 0.79; trust (e.g., “my spouse is thoughtful of my needs”) yielded alpha = 0.88; standing (e.g., “even when my spouse is angry, she treats me respectfully”) yielded alpha = 0.81; and voice (e.g., “my spouse makes a point of hearing my opinion before making important decisions”) yielded alpha = 0.79. The correlations among PPJ's elements in the current study were high ( r = 0.55–0.76) and, because previous studies used an average total PPJ score (Tyler, Degoey, and Smith ; Tyler ; Nelson et al ), we also computed a PPJ score based on the entire set (alpha = 0.93).…”
Section: Methodsmentioning
confidence: 84%
“…We note that we tested how each scenario affected the perceptions of all four dimensions of PPJ. We did this because PPJ dimensions had previously been highly correlated (former studies also averaged them into a unified PPJ score: Tyler ; Nelson et al ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations